Collaborative Virtual Environment to Facilitate Game Design Evaluation with Children with ASC. Issue 8 (9th May 2019) - Roper, Tessa; Millen Dutka, Laura; Cobb, Sue; Patel, Harshada
ABSTRACT: Involvement of children with autism spectrum conditions (ASC) in the design of new educational technology is becoming more prevalent. Despite potential barriers due to communication and ideation difficulties for children with ASC, adapted participatory design methods can successfully facilitate their direct involvement. Nonetheless, methods requiring face-to-face communication can still be difficult for children with ASC and research suggests that technology mediation could facilitate their contribution. This study explores the use of collaborative virtual environments (CVEs) as a medium through which students evaluated existing computer games and offered suggestions for game development. CVEs in which the users were represented by (a) avatars and (b) video-pods were compared to a face-to-face condition. Twelve typically developing (aged 8–9 years), 12 higher ability ASC (12–14) and 4 lower ability ASC children (12–14) participated. All student groups preferred the video-pod CVE and students with ASC were generally better able to contribute effectively through this medium than face-to-face.